Prevalence of cerebral amyloid angiopathy and its correlation with Alzheimer's disease and cognition in an autopsy‐confirmed cohort from China - Xiang‐Sha Yin; Jianru Sun; Xue Wang; Wei Wu; Zhen Chen; Di Zhang; Yuanyuan Xu; Yongmei Chen; Wenying Qiu; Xiaojing Qian; Jun Ni; Chao Ma (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract BACKGROUND We aimed to investigate the prevalence of cerebral amyloid angiopathy (CAA) and its correlations with Alzheimer's disease (AD) and cognitive impairment in an autopsy‐confirmed cohort donated to a human brain bank in Beijing, China. METHODS A total of 483 subjects were neuropathologically evaluated based on standardized protocols. Descriptive statistics and ordinal logistic regression models were used to estimate the correlation between CAA, AD, apolipoprotein E (APOE) genotyping, and cognitive function proximal to death. RESULTS Neuropathological assessment revealed that 53 of 483 subjects (11%) had CAA without AD, 78 of 483 (16%) had AD without CAA, 98 of 483 (20%) had both CAA and AD, and 254 of 483 (53%) had neither condition. A significant correlation was confirmed between CAA severity and AD. Subjects with both CAA and AD exhibited aggravated cognitive impairment. DISCUSSION Our results indicate a substantial prevalence of CAA that is frequently comorbid with AD and may exacerbate cognitive decline in the elderly population in China. Highlights First reporting of cerebral amyloid angiopathy (CAA) based on an autopsy‐confirmed cohort from China. The prevalence of CAA was high in the elderly Chinese sample. Age and apolipoprotein E (APOE) ε4 allele were related to the prevalence of CAA. CAA and Alzheimer's disease (AD) were frequently co‐occurred and significantly associated. Subjects with both CAA and AD exhibited aggravated cognitive impairment.